Сравнительный анализ биокинематической структуры техники переворота с захватом двух рук сбоку борцов вольного стиля различной квалификации - Тупеев, Юлай; Tupeev, Yalay (Східноєвропейський національний університет ім. Лесі Українки, 2012)
Представлена информация о биомеханической структуре техники переворота с захватом двух рук сбоку борцов вольного стиля различной квалификации. Установлены специфические особенности выполнения данного приёма, присущие спортсменам различной квалификации. На основании данных констатирующего эксперимента разработаны модельные характеристики длительности фаз, результирующей скорости центров масс различных биозвеньев тела спортсменов в весовых категориях 55–66 кг и 84–96 кг при проведении переворота с захватом двух рук сбоку. Определены перспективы дальнейших биомеханических исследований базовой техники двигательных действий борцов вольного стиля различной квалификации. Given information about biomechanical structure of turns technics with two-arm grip among freestyle wrestlers of different qualifications. We have defined peculiarities of execution of this hold that were peculiar for sportsmen of different qualifications. On basis of this experiment there were developed model characteristics of phase duration that resulted in speed of mass centers of different bio-links of sportsmen’s bodies in weight categories 55-66 kg and 84-96 kg while performing turns with two-arm grip from the side. We have also defined perspectives of further biomechanical researches of basic technics of motion actions of wrestlers of freestyle of different qualifications.
Comparative Analysis of Bio-kinematic Structure of Turn Technics with Two-arm Grip Among Freestyle Wrestlers of Different Qualifications
Keywords: спортивная техника; биомеханический анализ; моделирование; борцы вольного стиля; sports technics; biomechanical analysis; modeling; freestyle wrestlers